Psychoeducation in Adolescent Attitudes Towards Health - Alberta Listiyani Siegit (ANIMA Indonesian Psychological Journal, 2015)
One of the important things which determine the quality of young generation is holistic health, which includes five interrelated dimensions. Unfortunately, young people‟s concern and attitude toward health related matters is still poor. Therefore, this study aimed to look at the effect of psycho-education in adolescent attitudes towards health. It used an experimental research method which involved 26 students on 12th grade at St. Carolus Senior High School Surabaya. Measurement of adolescent attitudes towards health used a questionnaire compiled by the author (Cronbach's Alpha = .922 and KMO & Bartlett’s Test = .717). The results were analyzed using paired sample t-test showed t = - 2.767 and p = .010 which mean an increase in adolescent's attitude to health after the psycho-education was given. In general, it can be concluded that psycho-education could be a potential alternative method to enhance adolescents' attitude towards health.